A COMPARISON OF EFFICIENCY ON INTERVAL ESTIMATION OF VARIANCE ON NORMAL AND CONTAMINTED NORMAL DISTRIBUTIONS BY RESAMPLING TECHNIQUES - Supawnith, Kittikhun; Araveeporn, Autcha (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The objective of this research is to compare the efficient confidence interval of variance based on normal and contaminated normal distribution by sample variance method and resampling techniques consisted of jackknife and standard bootstrap methods. The data sample are generated from the normal distribution with the parameter of mean () 2 and variance () 2 and 6. The mean and variance of contaminated normal distribution are the same as the normal distribution, but proportion of contamination () is 0.1 and scale factor () is 2 and 5. The sample sizes () for this study are set as 10, 20, 30 and 50, and the 95% and 99% confidence intervals.The simulated data is generated by R program and repeated 1,000 times in each situation. The criterion to consider the best confidence interval is a minimum value of average width. On normal distribution, the results are shown that sample variance method is the best confidence interval estimation. For contaminated normal distribution, jackknife and standard bootstrap methods outperform the sample mean method, and the standard bootstrap method has the average width narrower than jackknife method.